9-c-2=3-c

Multiply both sides of the equation by -2.

9-c=3⋅(-2)-c⋅-2

Remove parentheses.

9-c=3⋅(-2)-c⋅-2

Multiply 3 by -2.

9-c=-6-c⋅-2

Multiply -2 by -1.

9-c=-6+2c

9-c=-6+2c

Subtract 2c from both sides of the equation.

9-c-2c=-6

Subtract 2c from -c.

9-3c=-6

9-3c=-6

Subtract 9 from both sides of the equation.

-3c=-6-9

Subtract 9 from -6.

-3c=-15

-3c=-15

Divide each term in -3c=-15 by -3.

-3c-3=-15-3

Cancel the common factor of -3.

Cancel the common factor.

-3c-3=-15-3

Divide c by 1.

c=-15-3

c=-15-3

Divide -15 by -3.

c=5

c=5

Solve for c (9-c)/-2=3-c